A 4-Year-Old Child with a Giant Cerebral Hydatid Cyst: A Case Report - CANİZCİ ERDEMLİ, PINAR (My University, 2024)
Echinococcosis is the most common cestode infection globally caused by the Echinococcus species. The most common organ involvement is the lungs and liver, but other organs can be rarely involved. Here, we present a case with a giant cerebral hydatid cyst. A 4-year-old boy presented with abnormal gait and walking at Marmara University School of Medicine Pendik Training and Research Hospital, Istanbul, Türkiye in September 2022. Cranial magnetic resonance imaging showed a cyst of 13 cm in diameter. The cyst was enucleated successfully with no rupture. Oral albendazole therapy was started. There was no eosinophilia, and the echinococcal indirect hemagglutination test was negative. Ultrasonography detected an anechoic cystic lesion in the liver. He was evaluated for deep-organ involvement; however, no cysts were detected in other organs. The histopathological examination was compatible with a hydatid cyst. Although intracranial hydatid disease in children is rare, it should be considered among the differential diagnoses in patients with neurological symptoms, especially in endemic regions.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Pediatrik Enfeksiyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Pediatrics Infectious Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Pediatri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Pediatri, Perinatoloji ve Çocuk Sağlığı; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pediatrics; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Pediatrics, Perinatology and Child Health; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine